Minangkabau Dalam Pendidikan Kota Padang Panjang - Thulus Gajay Syahbana; Muhammad Ridwan Efendi; Darul Ilmi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
In Minangkabau tradition, there are many areas related to human life, including education. Therefore, in this research the researcher discusses Minangkabau customs in the world of special education in Padang Panjang City. Taken from various books, journals, as well as interviews with several people who have competence about Minangkabau customs in Padang Panjang City, West Sumatra Province, as well as several documentation. So, this research itself will aim to explain and introduce widely about one of the education areas in Minangkabau, namely the city of Padang Panjang, to the wider community. This research itself is a descriptive literature study with a qualitative approach. The results of this research itself are that education in Minangkabau customs is actually not much different from the definition of education in general, because the aim of custom itself is to regulate humans to behave in accordance with customary rules that have been mutually agreed upon and in the current curriculum, Minangkabau customs have become local content in the independent curriculum. , in the form of theory and practice. The practitioners are from the indigenous people of Padang Panjang City